Capturing life histories about movements into and out of poverty: A road with pits and bumps. (May 2018) - Schiettecat, Tineke; Roets, Griet; Vandenbroeck, Michel
In order to take into account the power imbalances typically implicated in knowledge production about the complex social problem of poverty, social work researchers have increasingly acknowledged the importance of grasping the viewpoints and perspectives of people in poverty situations. In this contribution, we accordingly reflect on a current life history research project that retrospectively explores the life stories of parents with young children with regard to their mobility into and out of poverty that is examined in dynamic interaction with social work interventions. In this article, we discuss methodological and ethical challenges and complexities that we unexpectedly encountered in our research venture, as illustrated by three exemplary vignettes. These examples demonstrate issues of power between the researcher and the research participants that are not only inevitable, but also generate dilemmas, struggles and ambiguities that often remain underexposed in the ways scientific insights are reported. Rather than disguising these pits and bumps, we argue for a reflexive research stance which makes these issues of power in knowledge production susceptible to contemplation and scrutiny.